Non-specific factors of children protection with streptococcal tonsillitis and infected with herpes virus type 6 - Olkhovska, Viktoriia; Yeloyeva, Zalina; Olkhovskyi, Yevhen (ScienceRise: Medical Science, 2021)
The aim of the work was to study the characteristics of the response of non-specific protective factors in tonsillitis of streptococcal etiology in children infected and uninfected with HHV-6 infection at different periods of the disease. Materials and research methods. In 78 children aged 3–15 years, inflammation markers and phagocytic activity of peripheral blood neutrophils (PAN) were determined using the nitroblue tetrazolium reduction test. The studies were carried out in the acute period and in the period of convalescence. Mathematical and statistical processing of the data obtained was carried out using Microsoft Excel 2003 and Statistica 6.0 programs. The significance of differences between the mean values was determined using the Student's test (t). Results. It was found that infection of children with HHV-6 leads to a decrease in the functional activity of neutrophils in the onset of streptococcal tonsillitis compared with uninfected patients (p<0.05). Also, the acute period of streptococcal tonsillitis in patients with co-infection is accompanied by a violation of the functional reserve of the oxygen-dependent mechanism of bactericidal neutrophils: minimal opportunities were found in tonsillitis on the background of HHV-6 infection (p<0.05). By the period of convalescence, a decrease in the indicators of the functional activity of neutrophils, increased in the acute period, was recorded, but in children infected with HHV-6, a complete recovery of indicators to the physiological norm did not occur. One of the features of streptococcal tonsillitis in children with HHV-6 infection is an increase in serum gamma globulin level (p˂0.05), lack of significant dynamics of decrease in the ASL-O indicator. Conclusions. The presence of VHL-6t infection in a child with streptococcal tonsillitis adversely affects the state of nonspecific protective factors, in particular PAN. The obtained data must be used to optimize the management of patients at different periods of the disease, including at the stages of dispensary observation